European asylum law. Reality and challenges in the context of immigration - Carvalho, Ana Celeste (2016)
The protection of the rights of refugees and asylum seekers has become an important issue in legal discourse. This is primarily due to rising migration levels, precipitated by greater political and economic instability in overseas nation states such as Syria for example, which has been embroiled in a protracted civil war that has left the country in shambles and its people with no hope for the better future. As a result of large-scale migratory movements in the EU space today, it is a major challenge for Member States to comply with the Geneva Convention and EU law concerning the protection of refugees and asylum seekers.